2007
DOI: 10.1210/en.2006-1272
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor (IGF)-I Controls Prostate Fibromuscular Development: IGF-I Inhibition Prevents Both Fibromuscular and Glandular Development in Eugonadal Mice

Abstract: Although antiandrogen therapy has been shown effective in treating prostatic tumors, it is relatively ineffective in treating benign prostatic hyperplasia (BPH). In an attempt to understand better the role of androgens in the development of the normal prostate and BPH, we studied the relative effects of testosterone and IGF-I on the development of the two compartments of the prostate in castrated IGF-I((-/-)) male mice. Here we report that IGF-I stimulated the development of the fibromuscular compartment, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…In a previous study, mice with global inactivation of the Igf1 gene displayed impaired development of the glandular prostate compartment (Ruan et al 1999). In a later study, it was shown that IGF1 can affect the development of both prostate compartments (Kleinberg et al 2007). In the present study, there were reductions in glandular size and luminal area, as well as a reduction in the FMS compartment surrounding the glandular structures in the VP and DLP lobes of LI-IGF1 K/K mice.…”
Section: Control Mice Li-igf1supporting
confidence: 63%
“…In a previous study, mice with global inactivation of the Igf1 gene displayed impaired development of the glandular prostate compartment (Ruan et al 1999). In a later study, it was shown that IGF1 can affect the development of both prostate compartments (Kleinberg et al 2007). In the present study, there were reductions in glandular size and luminal area, as well as a reduction in the FMS compartment surrounding the glandular structures in the VP and DLP lobes of LI-IGF1 K/K mice.…”
Section: Control Mice Li-igf1supporting
confidence: 63%
“…Studies also indicated that stroma play a pivotal role in prostatic epithelial pathogenesis . IGF‐1 stimulated the development of the fibromuscular compartment and local enforced IGF expression induced hyperplasia in prostate . The development of BPH preferentially occurs in the TZ of prostate .…”
Section: Discussionmentioning
confidence: 99%
“…17,18 IGF-1 stimulated the development of the fibromuscular compartment and local enforced IGF expression induced hyperplasia in prostate. [19][20][21] The development of BPH preferentially occurs in the TZ of prostate. 22 Interestingly, in the present study, we revealed that the expression of IGF-1 had no significant difference between TZ and PZ stroma of BPH, and our previous study showed that androgen treatment TRAF6 is an important adaptor molecule in various signaling pathway and possesses a broad spectrum of substrates.…”
Section: Discussionmentioning
confidence: 99%
“…The stromal‐to‐epithelial ratio is relatively constant at 2:1 from birth to 40 years of age in normal glands increasing to 5:1 in BPH . Embryonic reawakening , , imbalance between androgen and estrogen , chronic inflammation , , stem cell defects , and epithelial‐stromal interactions , have been implicated in the pathogenesis of BPH. Investigation of the morphological analogies between the fetal prostatic stroma and the BPH stroma nodules showed a similar developmental profile: from immature mesenchyme toward fibroblastic stroma, culminating in predominantly smooth muscle .…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of the morphological analogies between the fetal prostatic stroma and the BPH stroma nodules showed a similar developmental profile: from immature mesenchyme toward fibroblastic stroma, culminating in predominantly smooth muscle . Androgen/androgen receptor (AR) signaling plays an important role in BPH development by influencing the stromal cell paracrine factors that can regulate the adjacent epithelial growth and differentiation . Inversely, epithelial cells contribute to the increased stromal cell population via epithelial‐mesenchymal transition (EMT) , .…”
Section: Introductionmentioning
confidence: 99%